Inflammatory myopathy: diagnosis and clinical course, specific clinical scenarios and new complementary tools. (June 2015) - Selva-O'Callaghan, Albert; Trallero-Araguás, Ernesto; Martínez, Maria Angeles; Labrador-Horrillo, Moises; Pinal-Fernández, Iago; Grau-Junyent, Josep Maria; Juárez, Candido
<x xml:space="preserve">Abstract</x> Idiopathic inflammatory myopathies are a heterogeneous group of rare autoimmune diseases characterized by symmetric proximal muscle weakness and inflammatory infiltrates on muscle biopsy. A meticulously collected combination of clinical, serological, and pathological data is essential to correctly diagnose and classify myositis patients, often a considerable challenge for clinicians. This article provides a comprehensive overview of the most useful tools for the diagnosis and follow-up of patients with myositis. Capillaroscopy, serological biomarkers (particularly the autoantibody profile) and imaging techniques, such as muscle magnetic resonance and chest ultrasound, are of great aid in diagnosing, classifying and managing these patients. Relevant clinical scenarios, such as interstitial lung disease, associated cancer and pregnancy are also addressed in this review. Myositis registries, identification of new autoantibodies, and genetic studies will enhance our understanding of the pathogenesis of these conditions and help to define new diagnostic and therapeutic approaches.